An Analysis of Monetary Policies in an Uncertain Economic Environment in a Ugandan Perspective - Sunday, Arthur; Byamukama, Eliab; Ssekajugo, Derick (International Journal of New Technology and Research, 2017)
In recent years, progress in macroeconomic modeling was done to give new perspectives on the impact of uncertainty on the evolution of monetary policy. As, uncertainty is dominant, it is important to understand how alternative policies can be selected when the central bank cannot accurately observe the macroeconomic variables.. Therefore, the central bank of developing countries , must have at their disposal the tools for modeling the most accurate. For this reason, in this paper we try to determine the robust optimal monetary policy in an uncertain economic environment: First, we present the main types of uncertainties; we discuss the models used and their derivation. Then we show the techniques used, and how to introduce uncertainty. Finally, we present the optimal robust responses to different forms of uncertainty considered. Our approach is to estimate a dynamic macroeconomic model with three representations of the dynamics of inflation, each with microeconomic foundations for the data of the economy with Bayesian techniques. Our results show that the uncertainty of the structural parameters affect the dynamic solutions for the economy, but also on the objective functions of various agents, particularly that of the central bank. Indeed, the central bank will be more careful in certain circumstances. Increased caution with the weights carried by the interest rate in the loss function.
Keywords: Monetary Policies; Economic Environment